204k views
0 votes
Q.12
12. If f(x) = 4x - x2, then find f (a+1)-f (a-1).
1 Add File

Q.13​

User Slims
by
5.2k points

1 Answer

3 votes

Answer:


f(a+1) -f (a-1) = 8 -4a

Explanation:

Given


f(x) = 4x - x^2

Required:


f(a+1) -f (a-1)

First, we solve for
f(a+1)

This is solved by substituting a + 1 for x in f(x)


f(x) = 4x - x^2 becomes


f(a + 1) = 4(a + 1) - (a+1)^2

Open bracket


f(a + 1) = 4a + 4 - (a+1)(a+1)


f(a + 1) = 4a + 4 - (a^2 + a + a+1)


f(a + 1) = 4a + 4 - (a^2 + 2a+1)

Open bracket


f(a + 1) = 4a + 4 -a^2 - 2a -1

Collect like terms


f(a + 1) = 4 - 1 + 4a - 2a -a^2


f(a + 1) = 3 + 2a -a^2

Solving for
f(a-1)

This is solved by substituting a - 1 for x in f(x)


f(x) = 4x - x^2 becomes


f(a - 1) = 4(a - 1) - (a-1)^2

Open bracket


f(a - 1) = 4a - 4 - (a-1)(a-1)


f(a - 1) = 4a - 4 - (a^2 - a - a+1)


f(a - 1) = 4a - 4 - (a^2 - 2a+1)

Open bracket


f(a - 1) = 4a - 4 -a^2 + 2a- 1

Collect like terms


f(a - 1) = -4 - 1 + 4a + 2a -a^2


f(a - 1) = -5 + 6a -a^2


f(a+1) -f (a-1) becomes


f(a+1) -f (a-1) = 3 + 2a -a^2 - (-5 + 6a -a^2)

Open bracket


f(a+1) -f (a-1) = 3 + 2a -a^2 +5 - 6a + a^2

Collect like terms


f(a+1) -f (a-1) = 3 +5 + 2a - 6a -a^2 + a^2


f(a+1) -f (a-1) = 8 -4a

User Camille
by
5.1k points